Changes in the Mathematics Learning Process During the Covid-19 Pandemic at Junior High School in Bukittinggi - Firmanti, Pipit; Yuberta, Fauzi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The spread of Covid-19 has affected every sector, including education. The learning process that used to take place in the classroom has now become virtualized. However, this exacerbates pupils' difficulties in learning mathematics, which they previously considered challenging even in offline learning activities. To deal with this challenge, it is vital to describe alterations in the learning process under this pandemic situation. This qualitative research was carried out through interviews and questionnaires. The participants were seven teachers and seven students from various junior high schools in Bukittinggi with varying accreditation. Structured interviews, both online and in-person, were used to collect data. The result shows that students could understand the subject better before the pandemic. During the pandemic, the percentage of students who understood the material learning decreased by 10%. However, the percentage of people who use online media as a learning resource has increased by 50%. Overall, the assessment done by teachers on the cognitive aspects of a pandemic by Minimum Completeness Criteria (MCC) remains at 75. In the future, there will be a trend toward the use of e-learning and the development of technology-based learning media in the classroom.Penyebaran wabah Pandemi Covid-19 telah berdampak pada semua sektor termasuk pendidikan. Proses pembelajaran yang awalnya berlangsung tatap muka sekarang beralih secara virtual. Padahal sebelum pembelajaran daring dimulai, siswa masih kesulitan dalam mempelajari matematika. Oleh karena itu, mendeskripsikan perubahan apa saja yang ada selama proses pembelajaran daring penting dilakukan untuk mengatasi masalah ini Penelitian ini merupakan penelitian kualitatif dimana sampel diambil adalah tujuh orang guru dan tujuh orang siswa SMP/MTsN dari sekolah yang memiliki akreditasi berbeda di Bukittinggi. Pengambilan data dilakukan dengan wawancara terstruktur via online dan tatap muka. Berdasarkan hasil penelitian diperoleh: siswa lebih mudah memahami materi pelajaran yang disampaikan oleh guru sebelum pandemi. Persentase dalam pemahaman siswa terhadap materi yang diajarkan guru turun sebanyak 10 % selama pandemi. Sebaliknya, persentase dalam penggunaan media online sebagai sumber belajar meningkat sebanyak 50 %. Secara keseluruhan, penilaian yang dilakukan guru cenderung pada aspek kognitif selama pandemi dengan Kriteria Ketuntasan Minimum (KKM) tetap 75. Dimasa yang akan datang, akan ada tren penggunaan e-learning di sekolah dan pengembangan media pembelajaran berbasis teknologi.